Effect of post-harvest maturation treatment on germination and potential longevity of pepper (Capsicum annuum) seeds - Demir, I; Okcu, G (The Indian Journal of Agricultural Sciences, 2005)
A study was conducted during 2001 and 2002 to examine the effect of post-maturation treatments on germination and longevity (Ki of the viability equation) of variety 'Sera Demre' of chilli (Capsicum annuum L.) seeds. Fruits were harvested when they were green, orange and red. Seeds were extracted immediately after harvest and dried at 20 degree Celcius for 5 days, 25 degree Celcius for 21 days or allowed to remain in the fruits for 14 days and dried. Maximum advantage was obtained from post-harvest maturation in which seeds were allowed to remain in the fruits for 14 days. This treatment increased germination from 17-21% to 72-80% in seeds of green fruits, from 51-55% to 89-93% in orange, 75-78% to 83-87% in red fruits in 2001 and 2002 respectively. The lowest (Ki) values in all harvest and treatment combinations were found in seeds extracted immediately after harvest from green fruits and dried at 20 degree Celcius as -1.67±0.19 and -3.19±0.51. The maximum longevity of 1.38±0.00 and 1.31±0.07 was observed in treated seeds of red in 2001 and orange fruits in 2002 respectively. The maximum germination and longevity of pepper seeds were obtained when seeds retained within the fruit for 14 days following harvest.